Evaluation of a wheat protein concentrate for finishing swine - Allee, G.L.; Deyoe, C.W.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments involving 66 finishing pigs were conducted to determine the feeding value of a wheat protein concentrate. Pigs fed diets containing as much as 60% wheat protein concentrate consumed the same quantity of feed, gained at the same rate, and were just as efficient in feed utilization as pigs fed the control diet. Pigs fed the diet containing 96.1% wheat protein concentrate consumed less feed and gained significantly slower (P<.05) than pigs fed the control diet. Extrusion processing of the wheat protein concentrate gave no beneficial effect on feed intake, daily gain or feed required per unit of gain. It appears that up to 60% wheat protein concentrate may be used in finishing pig diets with no adverse effects.
Swine Industry Day 1972 is known as Swine Day 1972
Keywords: Swine; Wheat protein; Finishing pigs